Empirical Encyclopedia of Informal Workers - Svetlana Barsukova (Journal of Economic Sociology, 2014)
The author presents a review of “In the Shadow of Regulation: Informality in the Russian Labor Market” edited by V. Gimpelson and R. Kapeliushnikov (HSE Publishing House, 2014). This book is designed as a collection of texts devoted to various aspects of informal employment in the Russian labor market. The book review attempts to explore whether informal employment can be treated as a result of imperfections in the formal employment system or a special sector that helps to overcome those shortcomings. To answer this question, the author turns to basic definitions in order to understand who can be described as "informally employed". Different approaches to defining informality are given. Then, based on empirical results, it’s demonstrated that the position of "informally employed" сan be better as well as worse, compared to "formal employment". The lack of social guarantees can be considered the most evident shortcoming of being informally employed, while saving money due to the absence of taxation can be seen as a key advantage. There are though countries with both higher and lower incomes among the informally employed in world markets. Turning to Russian realities one should pay attention to the heterogeneity of informal employment: in general, informally employed workers have lower incomes, but some groups, such as freelancers, earn more money. The self-estimation of informally employed people does not prove the idea of informal employment as a problem to the employed themselves as they do not assess their status as lower than being formally employed. Taking into account the variety of aspects of informality, it’s hard to assess it either positively or negatively, but it’s rather evident that the struggle against informality itself would be erroneous while the best way to reduce the informal sector is to correct the formal sector to make it more attractive.